(untitled) (Journal of Engineering, 2006)
Considerable concentrations of vehicular emissions at signalized intersections and streets, in urban area are health-related issues of concern to society in general. This paper presents an examination for the effect of vehicle driver behaviour on vehicular excess CO emissions. The examination process based on site observations. in Erbil City which, satisfy the objectives and specifications of this Four signalized intersections study selected, and the necessary traffic behaviour and vehicle exhaust emission data collected. The traffic data were collected using video recording technique and the Analytical Mobile Gaseous Emissions CART P8334 machine used to measure vehicle exhaust emission data. The required traffic data abstracted from video play back using EVENT computer program, which provide coded digital representation for the requisite traffic activities. The abstracted data stored on floppy disks in the form of digital computer files. These files processed using computer programs developed for this purpose to abstract the necessary information from the raw data. Among the obtained traffic information are vehicle data classified according to the type of fuel used into two classes. The first class is gasoline powered vehicles which consisted of taxis and private cars covering different model year, engine condition and size, type of fuel injection system, number of cylinders. These data observed under different ambient air temperatures. The second class is the diesel-powered vehicles, which consists mainly of truck type vehicles. Following the processing stage, the obtained data presented and analyzed statistically to evaluate of the relationship between driver behaviour and vehicle excess of CO emission. Among the driver behaviours studied is queuing driver behaviour, which showed reasonably good relationship with the excess CO emissions. The results of this study are useful for the Local Authorities, traffic engineers and transportation planners. This is because, the obtained results assist in the adoption of suitable method of intersection control for the purpose of reduction of CO emissions and hence, reduce level of this type of air pollution.